A Loud Noise - Han, Dong, 1961- (Xianggang guo ji shi ge zhi ye 2013., 2014)
Drawn from International Poetry Nights in Hong Kong 2013, A Loud Noise is a chapbook of poetry by Han Dong presented in English, and Chinese. A Loud Noise is also available, along with the chapbooks of other internationally renowned poets, in Islands or Continents (Eighteen-Volume Box Set). Selected poems from this volume are featured in the anthology Islands or Continents: International Poetry Nights in Hong Kong 2013.